Profitability and Efficiency Analyses of Small Scale Rice processing units in Ngoketunjia Division, North West Region, Cameroon. - M.J, Bime; D.E, Fon; S.B, Ngalim; J, Ongla (JOURNAL OF ADVANCES IN AGRICULTURE, 2014)
Rice production and processing over the years has been on an increase with more small holders entering the business. This study on profitability of processing and marketing of small scale rice processors had as objective to analyse the profitability levels of rice processing and marketing by small scale processors, determine the value added to the commodity at each stageÂ and also identify the constraints faced by these processors. The study used primary data collected using well-structured questionnaire from millers only, miller traders for white/parboiled rice through a multistage sampling technique. Results showed that the net processing income (3,151,201), value added (8,147,456) and efficiency (138) for miller-traders of white rice was highest, followed by miller-traders for parboiled rice and lastly millers only. Results further showed that millers only had Benefit/cost ratio of 0.4 indicating that milling only is not profitable due to small quantities milled, and high fixed cost. Miller-traders for parboiled rice had a benefit/cost ratio of 2.3 implying that their venture is most profitable. Based on the results, it was recommended that millers only should purchase large quantities of paddy to enable them reduce the overhead cost. Also the services of parboilers should reflect in the sales price of parboiled rice so that the parboiling services can be paid for.